Treatment of L5‐S1 Floating Calcified Lumbar Disc Herniation with Percutaneous Endoscopic Interlaminar Discectomy - GuoNing Gu; Teng Liu; HuiZhi Guo; YongChao Tang; ShunCong Zhang; ZhiDong Yang; YongXian Li; Kai Yuan (Orthopaedic Surgery, 2024)
Objective The floating calcified tissue in floating calcified lumbar disc herniation (FCLDH) is hard and often adheres to the dura mater, which can easily cause nerve root damage during surgery, making the operation challenging. We proposed the classification of FCLDH and a new technique for removing floating calcified tissue and reported the clinical efficacy and safety of this new technique in clinical practice. Methods From January 2019 to October 2021, 24 patients (13 males and 11 females, 46.4 ± 7.72 years) with L5‐S1 floating calcified lumbar disc herniation were treated with percutaneous endoscopic interlaminar discectomy (PEID). According to FCLDH classification, a total of Type Ia: nine cases, Type Ib: five cases, Type IIa: four cases, and Type IIa: six cases were included. The visual analogue scale (VAS) and Oswestry disability index (ODI) were recorded pre‐operatively and 3 days postoperatively, 6 months postoperatively, and at the last follow‐up. The postoperative curative effect was evaluated according to the modified MacNab criteria. Computed tomography (CT) and magnetic resonance imaging (MRI) of the lumbar spine were performed 3 days after surgery to evaluate the efficacy of the surgery. Results All patients successfully underwent PEID. The VAS and ODI scores at 3 days postoperatively, 6 months postoperatively, and at the last follow‐up were significantly improved and statistically significant compared to those of the preoperative period (p < 0.05). All the patients were followed up for 12–24 months (mean, 16.6 ± 4.6 months). At the last follow‐up, according to the modified MacNab criteria, 15 cases were excellent, eight were good, and one was fair. The combined excellent and good rate was 95.83% (23/24). Postoperative review revealed that all floating calcified tissues were effectively removed and the nerve roots were adequately decompressed without complications such as cerebrospinal fluid leakage and lumbar spine infection. Conclusion The classification of FCLDH we proposed can well guide the selection of surgical plans. PEID combined with floating calcified tissue removal technology has good efficacy in the treatment of L5‐S1 FCLDH, ensuring accurate removal of calcified tissue, reducing complications and improving the quality of life of affected individuals.